2022
DOI: 10.1016/j.adaj.2021.12.007
|View full text |Cite
|
Sign up to set email alerts
|

The effect of mouthrinses on severe acute respiratory syndrome coronavirus 2 viral load

Abstract: Background Considering the oral cavity a major entryway and reservoir for SARS-CoV-2, the aim of this study was to perform a systematic review of in vivo and in vitro studies to assess the effectiveness of mouthwashes on SARS-CoV-2 viral load. Types of study We searched PubMed, Web of Science, Scopus, MedRxiv, and bioRxiv databases, including in vitro and in vivo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 61 publications
(87 reference statements)
0
10
0
Order By: Relevance
“…The COVID‐19 pandemic prompted a dramatic closure or limitation of dental services worldwide, thus causing serious health and economic consequences (Marcenes, 2020 ). The increasing risks in SARS‐CoV‐2 transmission via saliva and respiratory secretions during dental procedures has led to the use of pre‐operating mouthwashes (Tadakamadla et al, 2021 ; Mendoza et al, 2022 ; Silva et al, 2021 ) as additional preventive measures together with physical barriers such as facial masks and facial barriers.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The COVID‐19 pandemic prompted a dramatic closure or limitation of dental services worldwide, thus causing serious health and economic consequences (Marcenes, 2020 ). The increasing risks in SARS‐CoV‐2 transmission via saliva and respiratory secretions during dental procedures has led to the use of pre‐operating mouthwashes (Tadakamadla et al, 2021 ; Mendoza et al, 2022 ; Silva et al, 2021 ) as additional preventive measures together with physical barriers such as facial masks and facial barriers.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 pandemic prompted a dramatic closure or limitation of dental services worldwide, thus causing serious health and economic consequences (Marcenes, 2020). The increasing risks in SARS-CoV-2 transmission via saliva and respiratory secretions during dental procedures has led to the use of pre-operating mouthwashes (Tadakamadla et al, 2021;Mendoza et al, 2022;Silva et al, 2021) as additional preventive measures together with physical barriers such as facial masks and facial barriers. SARS-CoV-2 is surrounded by a lipid envelope that includes spike (S) glycoproteins able to interact with cell receptors widely expressed in mucosal tissues, gingiva, tongue, and salivary glands (Carrouel et al, 2021;Hamming et al, 2004).…”
mentioning
confidence: 99%
“…The use of pre-procedural mouth rinses should be considered routine in clinical dental practice because it could prevent the spread of the virus by reducing the number of microorganisms released from patient's saliva during splatter [14]. In clinical trials, povidone-iodine-based mouth rinses appeared to be the most effective oral pre-procedural mouth rinse in the context for SARS-CoV-2 viral load reduction [15].…”
Section: Safety Precaution and Infection Control Practices Among Dent...mentioning
confidence: 99%
“…A systematic review in 2022 evaluated several types of mouthwash [ 55 ] and concluded that, after a povidone-iodine solution, CPC is the most effective in vitro and in vivo to reduce the viral load of SARS-CoV-2 in saliva. CPC has a substantivity of 2–5 h [ 56 ]. In vivo, research demonstrates that the viral pressure of the SARS-CoV-2 virus in the saliva is suppressed for up to 3–6 h after rinsing with CPC [ 57 , 58 ].…”
Section: Introductionmentioning
confidence: 99%